Implementasi model pembelajaran kooperatif tipe Teams Games Tournament (TGT) untuk meningkatkan motivasi belajar perkalian dan pembagian peserta didik kelas II SD - Rosa Trishantya Widyasari; Siti Istiyati; Anesa Surya (Universitas Sebelas Maret, 2019)
The purpose of this research is to improve student motivation by implementation of Teams Games Tournament cooperative learning model on multiplication and division learning. The type of this research is class action research that consist of 3 cycles. The subject of this research is 32 students of 2nd grade of SDN Prawit I No.69. Data collection techniques are conducted by questioner, observation, and interview. Data analysis technique that used is interactive analysis that consist of data collection, data reduction, data display, and verification. To determine the result of student learning motivation, this research used source and method triangulation. The result of this research shows that multiplication and division learning motivation of the students are increase. First cycle result is classical pass percentage reach 37.5%, it increase at second cycle become 68.75%, and in the last cycle reach 84.38%. Based on the data analysis result, the conclusion of this research is Teams Games Tournament cooperative learning model can improve multiplication and division learning motivation of 2nd grade student of SDN Prawit I No.69 in the academic year of 2017/2018. Implication of Teams Games Tournament cooperative learning model was conducted by five steps. They are class presentation, teams, games, tournament, and team recognition.Key word: Multiplication and Division Learning Motivation, Teams Games Tournament (TGT) Cooperative Learning Model